Recommendations and solutions to remove some barriers to the deployment of smart grid in Morocco - Rachid Habachi; Achraf Touil; Abdellah Boulal; Abdelkabir Charkaoui; Abdelwahed Echchatbi (International Journal of Power Electronics and Drive Systems (IJPEDS), 2019)
In this paper, we identify the current state and prospects of smart grids in Morocco. We begin by describing the current state of the Moroccan network, then we study the obstacles to the development of smart grids in Morocco and internationally. We conclude with recommendations and solutions to remove some barriers to the deployment of intelligent electrical networks in Morocco.